Membangun Kapasitas Keuangan Petani Jeruk Siam di Sambas melalui Integrasi Teknologi SIAPIK - Nazarudin; Wahyu Ningrum, Wulan; Tezar, Muhammad (Jurnal Pengabdian Masyarakat Manage, 2025)
Siamese oranges are a leading commodity in Indonesia, including in Sambas Regency, West Kalimantan, which produces the highest production in the region. Despite its great potential, citrus farmers maintain challenges in the financial management of their business, which is still done manually and unstructured. This hinders business desirability and appropriate decision-making. This study aims to improve the financial management capacity of citrus farmers through the use of the SIAPIK application, a financial recording system developed by Bank Indonesia. The research approach used the Asset-Based Community Development (ABCD) method which focuses on empowerment through the utilisation of local assets. This activity was carried out through three main stages: socialisation and training, intensive mentoring, and evaluation. The results show that farmers who previously did not have organised financial records are now able to use the SIAPIK application to regularly record transactions, such as income, expenses and debts. Farmers' ability to read and analyse financial reports has also improved, which helps them plan financing and optimise farm management. This research shows that technology-based approaches and community empowerment can improve financial and technological literacy among farmers. In addition, the programme contributed to farm business efficiency, increased income and financial independence of citrus farmers in Sambas. These results provide a technology-based empowerment model that can be replicated to support the economic welfare of the agricultural sector in other areas.